2017
DOI: 10.1016/j.rmed.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of multiple risk factors on asthma in school-aged children

Abstract: Background Little is known about synergistic effects of several risk factors on asthma. We developed a risk score in Puerto Rican children, and then used this score to estimate the combined effects of multiple risk factors on asthma at school age in Puerto Rican and Swedish children. Methods Case-control study in 609 Puerto Rican children (aged 6–14 years) and longitudinal birth cohort study of 2,290 Swedish children followed up to age 12 years (The Children, Allergy, Milieu, Stockholm, Epidemiological Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…Our findings add strong evidence to the only previously published study that investigated the association between childhood asthma and a combination of several adverse lifestyle factors 12. This small case–control study conducted among 609 Puerto Rican children aged 6–14 years showed that the presence of three risk factors compared with none was associated with 10-fold to 11-fold increased odds of asthma.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings add strong evidence to the only previously published study that investigated the association between childhood asthma and a combination of several adverse lifestyle factors 12. This small case–control study conducted among 609 Puerto Rican children aged 6–14 years showed that the presence of three risk factors compared with none was associated with 10-fold to 11-fold increased odds of asthma.…”
Section: Discussionsupporting
confidence: 81%
“…For example, Szentpetery et al initially developed a diagnostic model, identifying gun violence and an unhealthy diet as predictors of childhood asthma in a Puerto Rican population. However, when validated as a prediction model in a Swedish cohort, data for these two predictors were unavailable, potentially due to low concern for these risk factors in this population, and were excluded from the model 37 …”
Section: Discussionmentioning
confidence: 99%
“…AR represents a considerable burden on public health, impacting daily activities, quality of life and productivity . It is also frequently associated with various comorbidities, including asthma . AR often precedes asthma, with the progression from AR to asthma considered part of the “allergic march”, while uncontrolled AR may be associated with worsening of coexisting asthma …”
Section: Introductionmentioning
confidence: 99%